Evaluación Presupuestaria al Gobierno Autónomo Descentralizado Parroquial de Tundayme Periodo 2021-2022. - Encalada Paladines, Yulissa Dayanara (2024)
The present Curricular Integration Work called "BUDGETARY EVALUATION OF THE PARISH DECENTRALIZED AUTONOMOUS GOVERNMENT OF TUNDAYME, PERIOD 2021-2022", was executed according to an action plan that allowed evaluating the fulfillment of the annual Operational Plan based on the programmed and executed activities; and through the application of budgetary indicators; in order to measure the management of the Entity. Therefore, thanks to the implementation of an action plan, it was possible to determine whether the proposed projects were fulfilled. Subsequently, through the application of budget indicators, it was possible to determine the efficiency and effectiveness of the Entity in the management of resources and the degree of execution of the planned projects, by collecting the necessary information such as the Income and Expenditure budget tables, budget execution status and the annual operating plan for the periods 2021-2022. Therefore, based on the Annual Operating Plan (AOP), it was evident that the entity is not complying with the programmed activities, since during the 2021 period, 5 projects out of the 11 planned were completed, representing an execution of 45.45%; while for the 2022 period, 1 project out of the 13 planned was completed, with a percentage value of 7.69% of the executed projects. Regarding the implementation of the budget indicators, it could be seen that for both periods the group of accounts with excellent results were the current revenues, since they have been executed at 100%.